North Sea surface drifter data from Heincke cruise HE513 - Ruben Carrasco; Uwe John; Rohan Henkel; Jochen Horstmann (PANGAEA, 2018)
The drifters were deployed within the German Bight of the North Sea from the FS Heincke during cruise HE 513, which was performed from 2nd to 11th June 2018. The utilized drifters obtain their position via the Global Positioning System (GPS) and communicated their locations to the lab via Iridium (a global full ocean coverage bidirectional satellite communication network). Within the experiment, three Albatros drifters ODi were used. The ODi is a spherical shaped drifter, which has a diameter of 0.2 m, where only approx. 0.1 m are above the water surface when deployed. To enhance the drifters drag a sail was attached 1.5 m below the sea surface. Due to the very small area above the water surface the drifter path represents the current in the upper meter of the water column.